Impact of rotation on stellar models. Issue 8 (30th September 2016) - Meynet, G.; Maeder, A.; Eggenberger, P.; Ekstrom, S.; Georgy, C.; Chiappini, C.; Privitera, G.; Choplin, A.
Abstract: After a brief recall of the main impacts of stellar rotation on the structure and the evolution of stars, four topics are addressed: 1) the links between magnetic fields and rotation; 2) the impact of rotation on the age determination of clusters; 3) the exchanges of angular momentum between the orbit of a planet and the star due to tides; 4) the impact of rotation on the early chemical evolution of the Milky Way and the origin of the carbon‐enhanced metal‐poor stars.